Development of Karate Physical Test Instrument Category Comparison (Kumite) Ages 14-17 Years (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2020)
These failures need to be corrected through practice, this is important to support performance when on the field. To increase the ability to exercise can be determining factors for a person's ability. Means there are several essential factors to improve performance in order to achieve optimal sports performance. Based on the background of the problem and the suitability of the focus of the study, this research is oriented to the preparation of a series of physical tests: How is the preparation of an effective physical test instrument model for athletes in karate? Produce physical test norms of karate athletes aged 14-17 years to identify athletes in the karate sports competition category (Kumite)? Karate is a technique that gives everyone the freedom to use a fist or defend themselves barehanded. Karate is a martial arts branch that has been known for a long time in Indonesia and is a sport that is quite popular with the general public, both in large cities and in small areas. The method used to develop or validate Development products is in the form of a test which includes physical test measurements that can be used to identify karate athletes in the match category (kumite) aged 14 to 17 years. The basic consideration of this type of research and development is used to develop karate physical test instruments. The leg length factor has a dominant effect on karate play. The weight factor in this study is very influential in the game because the more relaxed the body is more freely in moving. The ideals in the body are very influential in karate motion skills. Reaction time test by Androi, Hexagone Obstacle Test, Hurdle Jump, Quick Strike, in this case the training method conducted by the researcher is the right method to measure and improve a physical ability of karate athletes, especially the kumite sparring category, age range of 14-17 years. Anaerobic capacity is determined by the maximum capacity of oxygen consumption and psychological capacity against physiological difficulties. How to train and measure the anaerobic abilities of karate athletes with Rust (Anerobic Running based anaerobic sprint test).